Contemporary accounting research : synthesis and critique : Journal of accounting and Economics Conference on Invited Critiques of Current Topics held 28-29, April, 2000 in Rochester, NY, USA - Kothari, S. P.; Journal of Accounting and Economics Conference on Invited Critiques of Current Topics (2000 : Rochester, NY) (Amsterdam ; Boston : Elsevier, 2002)
Provides a synopsis of the various accounting sub-fields and an analysis of the controversies. This book shows how, often, critique authors and their discussants express divergent opinions, and how such disagreement offers an encouraging signal that there remain interesting, open research questions and that our scholars find these issues exciting.
"Reprinted from the Journal of accounting and economics, volumes 31 and 32 (2001)."
Includes bibliographical references.
oif 27/03/15
Loan
Keywords: Accounting -- Research -- Congresses; Accounting